2020
DOI: 10.3389/fpls.2020.614871
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Hybrids Between Pelargonium × hortorum and Species From P. Section Ciconium Reveal Biparental Plastid Inheritance and Multi-Locus Cyto-Nuclear Incompatibility

Abstract: The genetics underlying Cyto-Nuclear Incompatibility (CNI) was studied in Pelargonium interspecific hybrids. We created hybrids of 12 closely related crop wild relatives (CWR) with the ornamental P. × hortorum. Ten of the resulting 12 (F1) interspecific hybrids segregate for chlorosis suggesting biparental plastid inheritance. The segregation ratios of the interspecific F2 populations show nuclear interactions of one, two, or three nuclear genes regulating plastid function dependent on the parents. We further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 74 publications
2
23
0
Order By: Relevance
“…Leaf material for DNA extraction was collected after 10 months. Pelargonium strains used were published previously (Breman et al 2020) and summarized in the supplementary materials (supplementary material 1).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Leaf material for DNA extraction was collected after 10 months. Pelargonium strains used were published previously (Breman et al 2020) and summarized in the supplementary materials (supplementary material 1).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Numerous studies point to nuclear genomic alleles being responsible for the occurrence of CNI in Ciconium (Tilney-Basset 1976, 1984, Metzlaff et al 1982, Tilney-Basset and Almouslem 1989, Tilney-Basset et al 1992, Apitz et al 2013, Horn 1994, Breman et al 2020 and co-evolution between functionally related genes was shown to occur (Zhang et al 2015. In Geraniaceae, and certainly in Ciconium, ERC seems to occur in genes controlling the ribosomal machinery (referred to here as: rERC) rather than the photosynthetic machinery (referred to here as: phERC).…”
Section: Evolutionary Rate Covariation Affects the Ribosomal Machinery In Ciconiummentioning
confidence: 99%
See 3 more Smart Citations